Tarjamah al-Kināyāt al-Qurʼānīyah ilá al-Lughah al-Tāmylīyah; Dirāsah Lughawīyah - Abdul Rauff, Mohamed Mahsoom; Abd. Rahman, Akmal Khuzairy (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2025)
This study aims to explore the methods used by Muslim translators in rendering metonymical (kināyāt) phrases from the Holy Qur'an into Tamil language, in light the of Mildred Larson's theory on translating metonymical expressions, with special attention to examining readers' levels of understanding of those Qur'anic texts, Making use of three approaches: the descriptive, analytical, and comparative approaches. The study concluded with findings, such as instances where all translators adopted the same approach in translating metonymical expressions. In other cases, the two translations were aligned, while their approaches differed in one case. In certain cases, the meaning intended in the original text was not adequately captured, which shows that relying on just one approach is inadequate for translating metonymy into Tamil. This research may pave the way for re-evaluating and reviewing the translation methodologies and techniques Adopted by translators in rendering Qur'anic metonymy into Tamil throughout the years that have passed. يهدف هذا البحث إلى تقصّي الأساليب التي اتخذها المترجمون المسلمون في ترجمة النصوص الكنائية من القرآن الكريم إلى اللغة التاميلية؛ في ضوء نظرية ملدرين لارسون في ترجمة التعبيرات الكنائية، مع عناية خاصة بتحرّي مستويات القراء في فهم تلك النصوص القرآنية، متوسِّلاً بثلاثة مناهج؛ المنهج الوصفي والمنهج التحليلي والمنهج المقارن. وقد توصّل البحث إلى نتائج، منها أنّ هناك مواضع اتّفق فيها كلٌّ من المترجمين على أسلوب واحد في ترجمة الكنايات، وهناك حالات أخرى تجانست فيها الترجمتان معًا، في حين تباينت أساليبهم في موضع واحد، وهناك مواضع لم تستوف المعنى المراد من النص الأصلي، مما يدل على أن الاعتماد على أسلوب واحد فقط غير كافٍ في ترجمة الكنايات إلى التاميلية. ولعلّ هذا البحث يفسح المجال لإعادة النظر والمراجعة في مناهج الترجمة وأساليبها التي سلكها المترجمون عند ترجمة الكنايات القرآنية إلى التاميلية طوال السنين والأيام التي انقَضَت.